A critical evaluation of the ecological / environmental programs of the Lower Mekong River Basin Plan - Cui, Jiuxu; I, Fude; Yamamoto, K.; Ahn, Kyu-Hong; DAAD (Bangkok : Asian Institute of Technology, 1988)
This study is an evaluation of the ecological environmental programs of the Mekong Committee. The evaluation includes an analysis of the characteristics of these programs along with the background information of the Lower Mekong Basin and the Lower Mekong Basin Plan. For this purpose the baseline information of the area, the necessary information about the Basin Plan and 1 4 ecological/environmental programs are reviewed and evaluated in terms of three criteria: ecological necessity, local condition as well as the feasibility for each program. A number of conclusions and recommendations have been drawn about the environmental programs of the Mekong Committee. It is clear that the environmental programs of the Mekong Committee appear to be spotty and disorganized and that as a result, the Committee should develop a complete plan for further ecological/environmental programs as soon as possible for the purpose of environmental conservation and the protection and improvement of the quality of life of the people in the Basin. It is also recommended that the Committee should give priority to the development of agriculture, agricultural oriented industries and related ecological/environmental programs.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Mekong River Basin -- Environmental aspects